Kualitas Pelayanan Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan di Puskesmas Sukodono Sidoarjo - Meisya Putri Dwiantoko; Imelda Dian Rahmawati (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
This study aims to determine the relationship between health facility measures and reference service measures on the quality of service for patients participating in BPJS Health at the Sukodono Community Health Center, Sidoarjo. This research also aims to describe the quality of BPJS Health services at the puskesmas. The results of previous research show that the quality of BPJS Health services at the Sukodono Community Health Center still needs to be improved, especially in the aspects of waiting time, patient satisfaction and communication with health workers. This research uses survey methods and data to find out how the quality of BPJS Health services at the Sukodono Community Health Center and how health facility actions and referral service actions influence service quality. It is hoped that the results of this research can become a reference for improving the quality of health services provided by the Sukodono Community Health Center, so that people who use BPJS Health services can receive better and more effective services.